2016
DOI: 10.17221/8820-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrolysed yeasts on ruminal fermentation in the rumen simulation technique (Rusitec)

Abstract: ABSTRACT:The objective of the present study was to investigate the effects of three different hydrolysed yeast products derived from Saccharomyces cerevisiae [hydrolysed whole yeast (HWY), less hydrolysed whole yeast (LHWY), and yeast cell wall (YCW)] on microbial fermentation characteristics using the rumen simulation technique (Rusitec) with three consecutive experiments. The Rusitec system consisted of six fermentation vessels. Each vessel received 5 g chopped meadow hay and 4 g concentrate (as-fed basis) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Supplementation with YHS shifted VFA profile from acetate to propionate, reducing the acetate:propionate ratio. Similar results have been recently reported by supplementing different YH to batch cultures (Kettunen et al, 2016) and Rusitec fermenters (Oeztuerk et al, 2016). The trend to reduced CH 4 production observed in YHS-fermenters in our study is consistent with the increased propionate proportions, as production of propionate serves as a competitive pathway for hydrogen.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Supplementation with YHS shifted VFA profile from acetate to propionate, reducing the acetate:propionate ratio. Similar results have been recently reported by supplementing different YH to batch cultures (Kettunen et al, 2016) and Rusitec fermenters (Oeztuerk et al, 2016). The trend to reduced CH 4 production observed in YHS-fermenters in our study is consistent with the increased propionate proportions, as production of propionate serves as a competitive pathway for hydrogen.…”
Section: Discussionsupporting
confidence: 92%
“…Rossi et al (2004) reported that the peptidic fractions of S. cerevisiae stimulated the growth of Megasphaera ehdenii, the major lactate utilizer in the rumen, and Meissner et al (2014) observed that a S. cerevisiae YH increased the growth of Megasphaera ehdenii and enhanced the in vitro ruminal fermentation of a high-fermentable substrate. More recently, Kettunen et al (2016) and Oeztuerk et al (2016) have reported the efficacy of a patented S. cerevisiae YH product to stimulate the in vitro fermentation of different diets in batch cultures and Rusitec fermenters, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported by Li et al [ 8 ], who also found increased production of SCFA using increasing levels of oligosaccharides (0.2 to 0.8%) in the basal diet of sheep. According to Pinloche et al [ 25 ], a rise in SCFA concentration may be related to increased metabolic activity by ruminal microorganisms, and stimulation of microbial growth, which is beneficial for the maintenance and production of the ruminant [ 26 ]. However, the accumulation and dissociation of SCFA in ruminal fluid lowers the pH, as observed in this experiment, which may cause morphological and histological changes in the ruminal papillae and thus impair the barrier function of the ruminal epithelium [ 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Total VFA at 0 and 4 h post feeding ranged from 118.4 to 118.6 mmol/l and from 118.5 to 118.7 mmol/l, respectively. However, some studies revealed that supplementation with yeast hydrolysate shifted the VFA profile from C2 to C3 and reduced the C2:C3 ratio in batch cultures (Kettunen et al, 2016) and Rusitec fermenters (Oeztuerk et al, 2016;Díaz et al, 2017).…”
Section: Indicesmentioning
confidence: 99%